Appraisal of Chicken Production with Associated Biosecurity Practices in Commercial Poultry Farms Located in Jos, Nigeria. (21st April 2016) - Maduka, C. V.; Igbokwe, I. O.; Atsanda, N. N.
Abstract : A questionnaire-based study of chicken production system with on-farm biosecurity practices was carried out in commercial poultry farms located in Jos, Nigeria. Commercial and semicommercial farms had 75.3% and 24.5% of 95, 393 birds on 80 farms, respectively. Farms using deep litter and battery cage systems were 69 (86.3%) and 10 (12.5%), respectively. In our biosecurity scoring system, a correct practice of each indicator of an event scored 1.00 and biosecurity score (BS) of each farm was the average of the scores of biosecurity indicators for the farm, giving BS of zero and 1.00 as absence of biosecurity and optimal biosecurity, respectively. Semicommercial farms had higher BS than commercial farms. The flock size did not significantly (p > 0.05 ) affect the mean BS. Disease outbreaks correlated (r = - 0.97 ) with BS, showing a tendency of reduction of disease outbreaks with increasing BS. Outbreaks were significantly (p < 0.05 ) associated with deep litter system. In conclusion, the chicken production system requires increased drive for excellent biosecurity practices and weak points in the biosecurity could be ameliorated by extension of information to farmers in order to support expansion of chicken production with robust biosecurity measures that drastically reduce risk of disease outbreak.